Novel clinical scores for occupational asthma due to exposure to high-molecular-weight agents. Issue 7 (20th April 2019) - Taghiakbari, Mahsa; Pralong, Jacques-André; Lemière, Catherine; Moullec, Gregory; Saha-Chaudhuri, Paramita; Cartier, André; Castano, Roberto; Suarthana, Eva
Abstract : Objective: Specific inhalation challenge (SIC) as the reference diagnostic test for occupational asthma (OA) is not widely available worldwide. We aimed to develop non-SIC-based models for OA. Methods: Of 427 workers who were exposed to high-molecular-weight agents and referred to OA clinic at Montréal Sacré-Cœur Hospital between 1983 and 2016, we analysed 160 workers who completed non-specific bronchial hyper-responsiveness (NSBHR) tests and still worked 1 month before SIC. OA was defined as positive SIC. Logistic regression models were developed. The accuracy of the models was quantified using calibration and discrimination measures. Their internal validity was evaluated with bootstrapping procedures. The final models were translated into clinical scores and stratified into probability groups. Results: The final model, which included age ≤40 years, rhinoconjunctivitis, inhaled corticosteroid use, agent type, NSBHR, and work-specific sensitisation had a reasonable internal validity. The area under the receiver operating characteristics curve (AUC) was 0.91 (95% CI 0.86 to 0.95), statistically significantly higher than the combination of positive NSBHR and work-specific sensitisation (AUC=0.84). The top 70% of the clinical scores (ie, the high probability group) showed a significantly higher sensitivity (96.4%vs86.9%) and negative predictive value (93.6%vs84.1%) than the combination of positive NSBHR and work-specific sensitisation (p value <0.001). Conclusions: We developed novel scores for OA induced by high-molecular-weight agents with excellent discrimination. It could be helpful for secondary-care physicians who have access to pulmonary function test and allergy testing in identifying subjects at a high risk of having OA and in deciding on appropriate referral to a tertiary centre.